Standard essential patents and the quest for faster diffusion of technology - Fredrik Erixon; Matthias Bauer (European Centre for International Political Economy (ECIPE), 2017)
Standard-essential patents (SEPs) have been critical to the ICT revolution. SEPs have allowed for the fast rates of innovation diffusion that the world has witnessed in the past 25 years. Yet the SEP system is under pressure. It suffers from a smoldering crisis of confidence as costly legal disputes across several international jurisdictions have caused unpredictable frictions in the markets for standardized technologies. Regulators in several parts of the world are now considering actions that seek to overcome obscurities in the SEP system. Asymmetric information is at the very heart of current problems in the market for SEPs, and all too often resembles a market dominated by a "confusopoly" with little transparency about products, quality and prices. In this paper, we will discuss ideas and concepts for what could be done to maintain a balanced and trusted system that supports technological innovation and at the same time conforms to economic efficiency.
Keywords: 330